THE INFLUENCE OF GOVERNMENT POLICIES ON THE GROWTH OF SHARIA BUSINESSES IN INDONESIA - Hermansyah, Yus; Heriyanto, Imron; Indrawanto, Setya; Hariadi, Fadli; Nuralam, Ikhsan (Universitas Efarina, 2023)
The government is actively conducting promotions and counseling related to the benefits and potential of sharia finance for the community and businesspeople. This is done through public campaigns, seminars, conferences, and exhibitions introducing Islamic financial products and services. This study aims to analyze government policies' influence on Sharia businesses' growth in Indonesia. The research method used is library research, with a qualitative approach. Data is collected based on observation and documentation and then analyzed through qualitative data analysis. The study results show that government policies also include efforts to educate and promote Islamic finance to the wider community. This includes social campaigns, training, and other programs that aim to increase understanding and awareness of the benefits of Islamic finance. The government is collaborating with the private sector, including Islamic financial institutions and other business actors, to develop a more inclusive and sustainable Islamic finance ecosystem. With the support and conducive policies from the government, the growth of Sharia businesses in Indonesia can continue to increase, make a significant contribution to the country's economy, and provide more diverse financial options by Sharia principles for the community.